The Ketogenic Diet and Its Effects on Patients With Type 2 Diabetes Mellitus – A Review Of Literature - Walczak, Anna; Kościuszko, Zuzanna; Sobiński, Adam; Czerwonka, Matylda; Kurza, Katarzyna; Podolec, Julianna; Ciraolo, Silvia; Agnieszka Kulczycka-Rowicka,; Wojda, Joanna; Lesiczka-Fedoryj, Katarzyna (Quality in Sport, 2025)
Purpose of the Study:This paper aims to analyze the impact of the keto diet on glycemic control, weight loss, medication use, and lipid profile in patients with type 2 diabetes (T2DM), as well as to assess its long-term safety and side effects. Research: This article is based on review of clinical trials, meta-analyses, and systematic reviews found on Pubmed, Google Scholar and other databases. After the evaluation of the articles, observational studies, experimental studies and meta-analyses, the key benefits and limitations of the keto diet in the T2DM were selected. Results:The keto diet improves glycemic control by lowering HbA1c, fasting blood glucose, and insulin resistance in T2DM patients. It also showed positive effects on lipid metabolism. In addition keto diet has been found to lead to greater weight reduction than other diets. This weight loss, along with improved metabolic parameters, often results in a reduced need for diabetes medications. However, there is limited data on the long-term safety and effectiveness of the keto diet for managing diabetes, and it may be difficult to maintain due to its strict carbohydrate restrictions. The diet’s strict limitations may also cause challenges for certain individuals, such as pregnant women, making it less sustainable for everyone. Furthermore, concerns include potential increases in LDL cholesterol and hypoglycemia, particularly during the initial stages of the diet. Additionally, the keto diet may lead to deficiencies in vitamins, minerals, fiber, and antioxidants, which are usually obtained from carbohydrates, making supplementation necessary to mitigate these deficiencies. Conclusions:The keto diet appears to be valuable for glycemic control, weight loss, and reducing medication use in T2DM patients. However, long-term data is lacking, and there are concerns about its sustainability and potential side effects, particularly regarding cardiovascular health and micronutrient deficiencies.